Liver Transplantation from a Donor with Multiple Biliary Hamartomata - Saidi, R. F. (Avicenna Organ Transplantation Institute, 2013)
Biliary hamartomata are rare benign lesions. Herein, we report on a 48-year-old man with a history of end-stage liver disease secondary to alcoholic liver disease. The patient received an orthotropic liver transplant from a brain-death woman. At the time of recovery, there were multiple lesions in the transplanted liver measuring 7–10 mm. Pathology revealed multiple biliary hamartomata. The postoperative course of the recipient was uncomplicated and he was discharged home 10 days after the transplantation.